The Exploring of Pro- Inflammatory Cytokine IFN- γ, IL-17 and TNF- α in Inflammatory Cytokine with Amoebic Dysentry from Kerbala Province - Jari, Sawsan Darweesh; Abbas, Zahraa fadhil (Eximia, 2025)
This research investigated the correlation between pro-inflammatory cytokines (IFN-γ, IL-17, and TNF-α) and Entamoeba histolytica infection in amoebic dysentery. The study examined the role of pro-inflammatory cytokines in preventing Entamoeba histolytica parasite infection. It measured IFN-γ, IL-17, and TNF-α concentrations in amoebiasis patients and compared them to healthy partisipants, demonstrating their importance. The study found a significant difference in IFN-γ, IL-17, and TNF-α concentrations in affected individuals (15.3 ± 1.5, 980.5 ± 23.4, and 29.4 ± 0.5 pg/ml) compared to the control group (6.5 ± 1.026, 658.6 ± 653, and 6.4 ± 0.9 pg/ml, respectively) (p ≤ p≤0.05). In addition, children ages 3-9 (78.5%) had the greatest infection rate, followed by 9–17 (71.4%), 24–30 (66.6%), and 17–24 (56.2%).. This research shows that amoebic dysentery patients had higher cytokine levels than healthy people. Age affects amoebic dysentery prevalence. Younger age groups, particularly children under 10, are more vulnerable to infection.